Urban Sustainability and Parking Areas in Naples. A Tool for Decision-Makers - Gargiulo, Carmela (TeMA - Journal of Land Use, Mobility and Environment, 2009)
The methodological target of this paper consists in setting up a supporting tool for the public decision-maker in individuating the areas for parking within urban territory. The construction of this tool is guided by criteria referring more to urban and regional planning choices than to transport ones and concerning mostly the integration among environmental safeguard, activities distribution and need for mobility. As matter of fact, the methodological route tends to join the morphological-settlement and environmental characteristics of the site with the demand for parking, which depends on the activities settled in the urban ambit of reference, considering them as key-elements in building compatible choices of city transformation either in the phase of localization, distribution and sizing of interventions or in the following phase of planning the building typology of parking equipments. This paper shares the position expressed in the report on sustainable European Cities, destined to the local authorities of any city in the states of the European Union, which belongs to those documents targeted to affect the development and implementation of innovating policies and actions for promoting a more sustainable urban Europe. Therefore, the paper is divided into three parts. The first part defines the algorithm showing the iter through which it is possible to define feasible and compatible solutions for envisaging localization, distribution and typology of the areas and spaces to be realized. The second part, through the real implementation in a particular case, the city of Naples, deals with the definition of further criteria that are time by time implemented according to the urban context of reference. The tird part deals with the application to Naples and individuates a specific typology of parking areas, as implementation of the worked out algorythm and of the above-said criteria. The central part of the paper deals, then, with defining a route through which, among the possible transformations, the feasible alternatives are univocally individuated according to the environmental, historical and geo-morphological compatibilities and on the base of the expressed demand. All the building process is targeted, from its beginning, to reach desired and chosen aims with the awareness, confirmed by the previous analysis phase, that there are limits, bonds and conditions circumscribing the field of physical transformation planning - concerning the parking realization in this case - within well defined boundaries. Although this paper shares the choice of mobility policies targeted to stop and discourage the vehicles transit in the city downtown and against the realization of parking in those areas, nevertheless the suggested algorithm leads to realize exclusively areas for residential parking in historical central areas.